Tiny Web Services for Sensor Device Interoperability - Priyantha, Bodhi; Kansal, Aman; Goraczko, Michel; Zhao, Feng (International Conference on Information Processing in Sensor Networks (IPSN '08), 2008)
There are many scenarios where interoperability is required for sensor devices. We demonstrate one approach to achieve interoperability: using web services. Hosting a web service challenges the batterylife, bandwidth, and processing power constraints of low power sensor nodes. We demonstrate a lightweight implementation on MSP430 based sensor nodes with 802.15.4 radios. The implementation allows standards compliant web service clients to use the sensors but minimizes code size and energy at the sensor nodes. It allows sensor nodes to enter sleep modes. We prototype an example application for a home sensor network along with two types of sensor nodes required for it. We also show how our system enables sensor nodes to be used easily from applications written in high level languages using existing development tools.